Non-inclusion complexes between riboflavin and cyclodextrins - de Jesus, Marcelo Bispo; Fraceto, Leonardo Fernandes [UNESP]; Florencia Martini, Maria; Pickholz, Monica; Ferreira, Carmen Verissima; de Paula, Eneida (Wiley-Blackwell, 2012)
Objectives To investigate the molecular interaction between beta-cyclodextrin (beta CD) or hydroxypropyl-beta-cyclodextrin (HP beta CD) and riboflavin (RF), and to test the anticancer potential of these formulations. Methods The physicochemical characterization of the association between RF and CDs was performed by UV-vis absorption, fluorescence, differential scanning calorimetry and NMR techniques. Molecular dynamics simulation was used to shed light on the mechanism of interaction of RF and CDs. Additionally, in-vitro cell culture tests were performed to evaluate the cytotoxicity of the RFCD complexes against prostate cancer cells. Key findings Neither beta CD nor HP beta CD led to substantial changes in the physicochemical properties of RF (with the exception of solubility). Additionally, rotating frame Overhauser effect spectroscopy experiments detected no spatial correlations between hydrogens from the internal cavity of CDs and RF, while molecular dynamics simulations revealed out-of-ring RFCD interactions. Notwithstanding, both RF beta CD and RFHP beta CD complexes were cytotoxic to PC3 prostate cancer cells. Conclusions The interaction between RF and either beta CD or HP beta CD, at low concentrations, seems to be made through hydrogen bonding between the flavonoid and the external rim of both CDs. Regardless of the mechanism of complexation, our findings indicate that RFCD complexes significantly increase RF solubility and potentiate its antitumour effect.
Keywords: cyclodextrin; NMR; non-inclusion complex; prostate cancer; riboflavin